One-Step Microwave Synthesis of Micro/Nanoscale LiFePO4/Graphene Cathode With High Performance for Lithium-Ion Batteries - Liu, Shulong; Yan, Ping; Li, Haibin; Zhang, Xiaobo; Sun, Wei (Frontiers in Chemistry, 2020)
The micro/nanoscale LiFePO4/graphene composites are synthesized successfully using one-step microwave heating method. One-step microwave heating can simplify the reduction step of oxide graphene and provide a convenient, economical and effective method for the preparation of graphene composites. The structure analysis shows that LiFePO4/graphene has high phase purity and crystallinity. The morphology analysis shows LiFePO4/graphene microspheres and micron blocks are composed of densely aggregated nanoparticles, the nanoparticle size can shorten the diffusion path of lithium ions, thus increase the lithium ion diffusion rate. And the graphene sheets can provide the rapid transport path for electrons, thus increase the electronic conductivity of materials. And the nanoparticles packed into the micron graphene sheets can ensure the stability in the electrolyte during the charging and discharging. Raman analysis reveals that graphene has a high degree of graphitization. Electrochemical analysis shows that the LiFePO4/graphene has an excellent capacity, high-rate performance and cycle stability. The discharge capacities are 166.3, 156.1, 143.0, 132.4 and 120.9 mAh g−1 at 0.1, 1, 3, 5 and 10 C rates, respectively. The superior electrochemical performance can be ascribed to the synergy of the shorter lithium ion diffusion path achieved by LiFePO4 nanoparticles and the conductive networks of graphene.